2018
DOI: 10.1111/pace.13573
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phase mapping and electrogram‐based driver mapping for catheter ablation in atrial fibrillation

Abstract: Introduction: Adjunctive driver-guided ablation in addition to pulmonary vein isolation has been proposed as a strategy to improve procedural success and outcomes for various populations with atrial fibrillation (AF). First, this study aimed to evaluate the different mapping techniques for driver/rotor identification and second to evaluate the benefits of driver/rotor-guided ablation in patients with paroxysmal and persistent AF (PerAF). Methods: We searched the electronic database in PubMed using the keywor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…A step towards better understanding of the clinical impact of different AF driver mapping methodologies has recently been performed by Lin et al in patients with PersAF. [ 28 ] Their meta-analysis confirmed that adjunctive driver-guided ablation in addition to PVI could improve one-year AF freedom and increase acute AF termination rate without a significant increase in potential complications. The benefit in PersAF ablation seems to be more evident using phase-mapping methodologies rather than electrogram-based driver mapping.…”
Section: Main Clinical Evidence Using Novel Mapping Methods For Af Abmentioning
confidence: 92%
See 2 more Smart Citations
“…A step towards better understanding of the clinical impact of different AF driver mapping methodologies has recently been performed by Lin et al in patients with PersAF. [ 28 ] Their meta-analysis confirmed that adjunctive driver-guided ablation in addition to PVI could improve one-year AF freedom and increase acute AF termination rate without a significant increase in potential complications. The benefit in PersAF ablation seems to be more evident using phase-mapping methodologies rather than electrogram-based driver mapping.…”
Section: Main Clinical Evidence Using Novel Mapping Methods For Af Abmentioning
confidence: 92%
“…The benefit in PersAF ablation seems to be more evident using phase-mapping methodologies rather than electrogram-based driver mapping. [ 28 ]…”
Section: Main Clinical Evidence Using Novel Mapping Methods For Af Abmentioning
confidence: 99%
See 1 more Smart Citation
“…The basket contact-mapping catheter has limited resolution, but is sufficient to record organized rotational/focal activity [ 59 , 60 ] and has been shown by others to be superior to prior methods [ 61 ]. It remains unclear which method for detecting AF phase singularities is optimal, but a recent meta-analysis supports the use of phase mapping for AF [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these substrate modification strategies, driver‐guided ablation has emerged as a potential therapeutic target for ablation of persistent AF. In a pooled meta‐analysis, the driver/rotor identification and ablation approach, despite using different mapping techniques and catheters, was associated with higher rates of acute AF termination (odds ratio [OR]: 4.62, p < .001) and lower rates of recurrence of any atrial arrhythmia (OR: 0.44, p < .001) 16 . We have previously reported that after PVI in patients with persistent AF, atrial substrate modification guided by SI and nonlinear phase mapping is associated with a lower AF recurrence rate compared with those receiving CFAE ablation 7 .…”
Section: Discussionmentioning
confidence: 99%